Oral non-Hodgkin's lymphoma as an initial diagnosis in a HIV positive patient - Elluru Venkatesh; Anjana Bagewadi; Vaishali Keluskar; Arvind Shetti (Wolters Kluwer Medknow Publications, 2008)
Patients with the acquired immunodeficiency syndrome (AIDS) present unique diagnostic challenges because of a propensity to develop unusual infections and neoplasms. Since the beginning of the AIDS epidemic, the number of documented clinical manifestations has considerably increased. Current estimates are that 40% of patients with AIDS have a malignant tumor at the time of initial diagnosis, and the percentage may increase to 70% over the course of the disease. It is generally recognized that Kaposi's sarcoma is the most common of these malignant conditions, but non-Hodgkin's lymphoma (NHL) is also being diagnosed in greater numbers. The purpose of this paper is to present one such case of oral NHL as initial diagnosis in a HIV positive patient.